The Influence of Chain Writing Method Increase Students' Writing Ability of Descriptive Text at Seventh Grade of SMPN 03 Kamal - Farida Windari; Mohammad Kurdi Wijaya (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2024)
This studied discusses the effect of using the Chain Writing method on the write skills of class VII students of SMPN 03 Kamal and the background is that there are students who are less skilled at write a text, so that students are gift a method that can increase the creativity of write texts. Besides that, the purpose of this studied was to find out whether the Chain Writing method had a significant difference or not on students' writing skills. In this study, researcher used a type of quantitative research that is experimental on the effect of using the Chain Writing method on improving the skills of writing descriptive text in Class VII students of SMPN 03 Kamal with a total of 20 students. This study collected data used a pre-test to determine students' write skills before being given treatment and a post-test to determine students' write skills after being given treatment. And used a random technique, namely taking students at random, namely class VII A students from four classes. Based on the results of the research is the method used by students of class VII is significant, then the method is efficient or good for learning, especially learning English. The results were obtained from 3.039 > 4.41, with pre-test and post-test scores increasing from 62.5000 to 73.5000. So it was concluded that students could increase their creativity or write skills by used the Chain Writing method for learning English.